3D particle-based DEM investigation into the shear behaviour of incipient rock joints with various geometries of rock bridges - Shang, Junlong (2020)
A 3D particle-based DEM model was established taking into account the geometries of rock bridges. The model was used to investigate the shear behaviour of incipient rock joints. Fifty-seven direct shear tests were conducted under constant normal load (CNL) boundary conditions using the established model, in which rock bridges with 19 different geometries and incipient joints with various areal persistence (between 0.2 and 0.96) were involved. Our results show that, for the cases having a single rock bridge, cracks often initiated around the edges of the rock bridges and coalesced first in the middle of the rock bridge areas. While for other cases containing multiple rock bridges, cracks initially appeared at the connection points (located in the middle of the joint planes) of the rock bridges and then propagated to the edges. High crack initiation stresses were measured, which were often more than 60% of the shear strength of the tested incipient rock joints. Sudden failures of the rock bridges subjected to shearing were observed, accompanying dramatic increases in the number of cracks. Another important conclusion derived from this research is that both joint areal persistence and rock bridge geometry played significant roles in the shear failure of the simulated Horton Formation Siltstone joints. The present study has shown that shear strength increased gradually when joint areal persistence was decreased. Interestingly, different shear strength values were measured for rock joints with the same areal persistence (e.g. K = 0.5). Shear velocity was also found to have a significant influence on the shear characteristics of the Horton Formation Siltstone joints. A higher shear strength was measured when the shearing velocity was increased from 0.01 to 1 m/s.